2016
DOI: 10.5812/asjsm.35776
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Curcumin Supplementation on Exercise-Induced Oxidative Stress

Abstract: Background: Polyphenols are a class of organic chemical compounds, with strong antioxidant capacity. This investigation evaluates the influences of one week curcumin supplementation on selected indices of oxidative stress after 14 km running in active healthy young males. Objectives: The aim of this study was to investigate the effects of 1 week of curcumin supplementation on anti-oxidant markers. Methods: Subjects were randomized in a double blind, placebo-controlled fashion into two groups: Curcumin (C) (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Qin et al 2018 [ 159 ] observed a significant reduction in MDA levels (SMD = −0.769; 95% CI −1.059 to −0.478) in seven publications [ 27 , 57 , 98 , 114 , 124 , 153 , 156 ]. Alizadeh et al 2019 [ 150 ] showed a significant reduction in MDA (SMD = −0.46; 95% CI −0.68 to −0.25) in 12 publications [ 27 , 43 , 98 , 124 , 143 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ].…”
Section: Resultsmentioning
confidence: 99%
“…Qin et al 2018 [ 159 ] observed a significant reduction in MDA levels (SMD = −0.769; 95% CI −1.059 to −0.478) in seven publications [ 27 , 57 , 98 , 114 , 124 , 153 , 156 ]. Alizadeh et al 2019 [ 150 ] showed a significant reduction in MDA (SMD = −0.46; 95% CI −0.68 to −0.25) in 12 publications [ 27 , 43 , 98 , 124 , 143 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ].…”
Section: Resultsmentioning
confidence: 99%
“…At moderate concentrations, it displays significant antioxidant and anti-inflammatory property (97,98). Studies have demonstrated that curcumin potentially reduces serum lipid peroxidation level and restore normal serum reduced glutathione (GSH) content in subjects participating in intense running (99). Curcumin reduces inflammatory reaction in mice performing full-body exercise (100), improves the antioxidant status in humans participating in exercise (101) and decreases muscle soreness and damage in participants performing moderate to high-intensity aerobic exercises (102).…”
Section: Application Of Antioxidants In Exercise and Sportsmentioning
confidence: 99%
“…52 Some studies have suggested that betalains have potential antioxidant and anti-inflammatory effects 23,55 and supplementation with beetroot has been proposed not only to improve exercise performance but also to protect against oxidative stress. 39 The betalains, and betanins in particular, are thought to be the most potent antioxidant molecules and have shown to attenuate ROS production and to stimulate the expression of antioxidant enzyme genes. 18 Specific interest in beetroots has arisen in the last years because it is a rich source of polyphenolic compounds and NO 3 -.…”
mentioning
confidence: 99%
“…18 Specific interest in beetroots has arisen in the last years because it is a rich source of polyphenolic compounds and NO 3 -. 39 Since NO 3 may serve as a precursor of NO, supplementation with beetroots could have beneficial effects on sports performance. 54 Furthermore, because of the potential involvement of NO in the damage and repair processes in skeletal muscle, it has been suggested that beetroot supplementation could enhance recovery after EIMD.…”
mentioning
confidence: 99%
See 1 more Smart Citation